Tiga Ajaran Hindu dalam Menumbuhkan Sikap Toleransi Antar Umat Beragama - Dena Agustina (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to discuss the three Hindu teachings in fostering an attitude of tolerance between religious communities. This research method uses qualitative research through literature study and content analysis. The results and discussion of this research are Hinduism and its development, the concept of tolerance in general, and Hindu religious teachings related to tolerance in religion. The conclusion of this study is that Indonesia is a plural country. This plurality can be seen from aspects of culture, language, race, ethnicity, and one of them is religion. Religious differences are often very sensitive differences for adherents. Conflicts between religions are not uncommon in Indonesia. So to overcome and prevent conflicts between religious communities, it is necessary to instill the values of tolerance in every human being. Tolerance itself is an attitude of mutual respect, letting, and respecting what is different from him. In every religion, of course, it is taught about the value of tolerance and mutual respect between religious people. One of them is in Hinduism, in Hinduism there are three teaching concepts that discuss the attitude of tolerance between humans, namely Vasudhaiva Kutumbhakam, Tat Twam Asi, and Tri Hita Karana.